Donald Barthelme’s “Report” and Michal Rovner’s Decoy series, or the Ongoing Art of Telling It Slant - Sandrine Dechaume (Sillages Critiques)
This article examines how two contemporary artists, American writer Donald Barthelme and Israeli filmmaker and photographer Michal Rovner use overexposure in order to denounce forms of televisual “brain damage.” In Barthelme’s short story, the emphasis is on excess and satire, whereas in Rovner’s Gulf War images, media representations of war are deconstructed through the use of overexposed and blurred imagery.